2017
DOI: 10.4172/2155-9600.1000572
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Nitrite Content in Fresh Spinach Leaves: Evidence for Nitrite Formation Caused by Microbial Nitrate Reductase Activity

Abstract: Nitrite (NO 2 -) contained in dietary foods has long been recognized for its toxicity as the causative agent of methemoglobinemia and also as a source of mutagenic nitrosamines. Because of these potential toxicities, nitrite as well as nitrate contained in foods and drinks are strictly limited by regulations in many countries. Recent studies have offered us to update our recognition of nitrite; nitrite is an important precursor for Nitric Oxide (NO) that is required for fundamental physiological activities inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…However, these results cannot exclude the role of bacteria that were initially present in these vegetables as they were deactivated as well by boiling. Recent report from Watanabe's lab showed the evidence of microbial NR involved in the formation of nitrite in spinach leaves during storage [8].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these results cannot exclude the role of bacteria that were initially present in these vegetables as they were deactivated as well by boiling. Recent report from Watanabe's lab showed the evidence of microbial NR involved in the formation of nitrite in spinach leaves during storage [8].…”
Section: Resultsmentioning
confidence: 99%
“…The intake of excess amount of nitrite is believed to cause increased risk of some cancers and methemoglobinemia in infants [6,7]. There are many reports on the nitrate and nitrite contents in retail leave vegetables [2,8,9]. In respect to nitrate and nitrite contents change in leave vegetables during storage, there are inconsistent and controversial results; some reports indicated that nitrate levels dropped and nitrite levels increased dramatically in leave vegetables during storage in a few days at ambient temperature, but nitrate and nitrite levels did not change significantly over 7 days of storage in a refrigerator [10,11]; some researchers reported that the nitrite content in spinach increased about 27% after being frozen for 6 months at -25°C while no significant change in nitrate content [12].…”
Section: Introductionmentioning
confidence: 99%
“…Roots are the rst places where nutrients are absorbed and translocated into shoots for chlorophyll synthesis. More root formation depends on several factors (Watanabe and Yamasaki, 2016;Goltsev et al, 2016). Response to limiting mineral elements, plants have the ability to allocate a greater proportion of their biomass to the root system (Slavin and Lloyd, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many crop plants, especially leafy vegetables, accumulate excessive nitrate in expanded leaves under low light conditions when the uptake of nitrate exceeds reduction at a high transpiration rate. Usually when the plants use the solar energy su ciently, the absorbed nitrate from the soil is reduced to nitrite by Nitrate Reductase (NR) in cytosol (Watanabe and Yamasaki, 2016). Nitrite translocated into the chloroplasts is converted to ammonium ion (NH 4 + ) by nitrite reductase (NiR) located in the chloroplasts and then ammonium ion is assimilated into amino acids (Watanabe and Yamasaki, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…NO is involved in this global cycle through the denitrification activities of soil bacteria. Both denitrifying and nitrifying bacteria produce inorganic nitrite (NO 2 − ) as an intermediate metabolite [ 124 , 125 , 126 ]. NO 3 − is absorbed by the roots, followed by being delivered to the green leaves where photosynthetic CO 2 assimilation takes place.…”
Section: Figurementioning
confidence: 99%